2004
DOI: 10.1177/00238309040470020401
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Spoken Words: Semantic Effects in Lexical Access

Abstract: Until recently most models of word recognition have assumed that semantic auditory naming effects come into play only after the identification of the word in question. What little evidence exists for early semantic effects in word recognition lexical decision has relied primarily on priming manipulations using the lexical decision task, and has used visual stimulus presentation. The current study uses semantics auditory stimulus presentation and multiple experimental tasks, and does not use priming. Response l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…This approach has been supported by numerous studies showing semantic effects including priming, concreteness/imageability, and valence, in lexical decision (e.g., Azuma & Van Orden, 1997; Binder et al, 2003; Kuchinke et al, 2005; Pexman, Hargreaves, Edwards, Henry, & Goodyear, 2007; Samson & Pillon, 2004). Importantly, at least some of those studies have emphasized that semantic factors are at play concurrently with word identification and not simply accessed after lexical processing (Forster & Hector, 2002; Marslen-Wilson, 1987; Tyler, Moss, Galpin, & Voice, 2002; Wurm, Vakoch, & Seaman, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…This approach has been supported by numerous studies showing semantic effects including priming, concreteness/imageability, and valence, in lexical decision (e.g., Azuma & Van Orden, 1997; Binder et al, 2003; Kuchinke et al, 2005; Pexman, Hargreaves, Edwards, Henry, & Goodyear, 2007; Samson & Pillon, 2004). Importantly, at least some of those studies have emphasized that semantic factors are at play concurrently with word identification and not simply accessed after lexical processing (Forster & Hector, 2002; Marslen-Wilson, 1987; Tyler, Moss, Galpin, & Voice, 2002; Wurm, Vakoch, & Seaman, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Evaluation, Potency, and Activity) affect word recognition as well (e.g. Vakoch & Wurm, 1997;Wurm, 2011;Wurm & Vakoch, 1996;Wurm, Vakoch, & Seaman, 2004a). However, there is still the question of how such effects work, as well as the broader theoretical question of what function they may serve.…”
mentioning
confidence: 99%
“…This is thought to stem from cognitive resources being automatically allocated to the processing of affective components of a stimulus, leaving less available for the primary task itself. In the context of word recognition tasks such inhibitory effects have been demonstrated (Vakoch & Wurm, 1997;Wurm, 2011;Wurm et al, 2004a), and so one might be inclined to expect similar inhibitory effects of Danger. However, it is important to point out that Danger is cut from a different conceptual cloth.…”
mentioning
confidence: 99%
“…In order to safeguard the construct validity of the task, it was important that the real words were known to the participants. As in previous studies (e.g., Luce, Pisoni, & Goldinger, 1990;Wurm et al, 2004), the learners' likely recognition of the words was determined through familiarity ratings. For the purposes of this study, the Coltheart familiarity rating scale (1981a) was used.…”
Section: L2 Word Recognition Efficiency Taskmentioning
confidence: 99%
“…Some researchers consider automatization to simply involve an acceleration in the process of word recognition. Therefore, in accordance with this viewpoint, a large number of previous studies (e.g., Dahan, Swingley, Tanenhaus, & Magnuson, 2000;Dejean de la Batie, 1995;Shiotsu, 2003;Wurm, Vakoch, & Seaman, 2004) have simply analyzed participants' response latencies when calculating automaticity. However, it has also been found that the hallmark of word recognition automaticity is not only shorter RTs but also more stable response latencies (Logan, 1988;Newell, 1991).…”
Section: Introductionmentioning
confidence: 96%